Web-Based Asset Management Information System for Enhanced Asset Tracking at The Land Office of Bireuen District - Rozzi Kesuma Dinata, Agus Maula Rizki (Jurnal Elektronika dan Teknologi Informasi, 2024)
The management and tracking of assets at the Land Office of Bireuen District have become increasingly complex, necessitating the development of a more efficient and systematic approach. This study proposes the design and implementation of a web-based Asset Management Information System (AMIS) to optimize asset tracking processes. The system aims to provide real-time asset data, improve accuracy, and streamline the management workflow. Key features include asset registration, location tracking, maintenance scheduling, and reporting capabilities. By utilizing web technologies, the AMIS ensures accessibility and ease of use for authorized personnel. The implementation of this system is expected to significantly enhance asset management efficiency, reduce human error, and provide comprehensive data analytics for better decision-making. Initial testing and feedback from users indicate a substantial improvement in the overall asset management process at the Land Office of Bireuen District.